2021
DOI: 10.1002/smm2.1047
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic metal‐organic frameworks

Abstract: Plasmonic metal‐organic frameworks are composite nanoparticles comprising plasmonic metal nanoparticles (NPs) embedded within a metal‐organic framework (MOF) matrix. As a result, not only the functionalities of the individual components are retained, but synergistic effects additionally provide improved chemical and physical properties. Recent progress in plasmonic MOFs has demonstrated the potential for nanofabrication and various nanotechnology applications. Synthetic challenges toward plasmonic MOFs have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 151 publications
(180 reference statements)
0
46
0
Order By: Relevance
“…[101][102][103][104] Due to the unique and tunable optical properties of plasmonic nanomaterials, plasmon-induced chemical reactions show different mechanisms and have potential advantages over traditional photochemical reactions. [105][106][107] Surface plasmon are the collective oscillation of conduction electrons in metallic nanostructures, such as Au, Ag, and Cu nanomaterials. [108] Since the oscillation frequency of electrons matches that of light waves, the localized surface plasmon resonance will be excited.…”
Section: Plasmon-mediated Reactionsmentioning
confidence: 99%
“…[101][102][103][104] Due to the unique and tunable optical properties of plasmonic nanomaterials, plasmon-induced chemical reactions show different mechanisms and have potential advantages over traditional photochemical reactions. [105][106][107] Surface plasmon are the collective oscillation of conduction electrons in metallic nanostructures, such as Au, Ag, and Cu nanomaterials. [108] Since the oscillation frequency of electrons matches that of light waves, the localized surface plasmon resonance will be excited.…”
Section: Plasmon-mediated Reactionsmentioning
confidence: 99%
“…The photocatalytic products, such as CO and organic chemicals (HCOOH, CH 3 OH and CH 4 ), require different redox potentials -3.50 eV for CO, -3.42 eV for HCOOH, -3.65 eV for CH 3 OH and -3.79 eV for CH 4 to initiate the photocatalytic CO 2 reduction (Figs. 4(a) and 4(b)) [15,39]. As for CO production, the twoelectron photoreduction process implies a relatively low kinetic barrier.…”
Section: Photocatalysismentioning
confidence: 99%
“…Currently, numerous studies have shown that MOF-based hybrid materials could afford multifunctional properties via hybridization with other functional materials (e.g., metal nanoparticles [113][114][115][116], polymers [117,118], and other MOFs [119,120]. Similarly, combining functional components with COFs to obtain COF-based hybrid materials has also attracted widespread concerns [121][122][123][124][125][126].…”
Section: Synthesis Of Mof and Cof Hybridsmentioning
confidence: 99%